Adopting International Entrepreneurial Finance Education to a Local Context. Issue 3 (3rd July 2018) - Pounder, Paul A.; Pounder, Tracy R.
ABSTRACT: The purpose of this article is to consider an approach to teaching entrepreneurial finance using proverbs. It explores a process framework with teaching strategies that provides prescribed guidelines on the key aspects that assist in teaching using this approach. This article demonstrates that teaching with proverbs creates the construct for linking prior knowledge (proverbs) to new entrepreneurial finance concepts in a meaningful way. It further highlights that entrepreneurial finance education in different regions around the world is most effective for students when it is tailored to the local culture of the region. The authors present five main entrepreneurial finance topics with two to three subheadings, each with proverbs accompanied by their related entrepreneurial finance concept. The article concludes that the use of proverbs in entrepreneurial finance instruction provides several benefits and that proverbs have the potential to become an effective teaching instrument in the fields of entrepreneurship and finance.